Research on the Impact of Live Commerce on Starbucks Consumer Satisfaction - Based on the Moderating Effect of Supervision Strength - Su, Yue; Ma, Zhuang; Yin, Xinyuan; Zhao, Yuehan; Qu, Yi (Journal of Asian Business Strategy, 2022)
This paper aims to analyze the impact of live commerce business on Starbucks consumers' purchase intention, explore the impact of consumer satisfaction preference on Starbucks consumers' purchase intention of coffee, and explore the influence of supervision strength and its moderating effect of live commerce on Starbucks customer satisfaction. On the basis of understanding the definition and relevant literature, reasonable assumptions are put forward. Then, this study used the hierarchical regression analysis tool to test the hypothesis and conducted a questionnaire survey on 1091 consumer groups who had the experience of watching live commerce and ordering shopping. Through correlation and regression analysis, this study found that supervision, live interactive effect, commodity quality and after-sales service are the key factors affecting consumers' satisfaction with Starbucks live delivery mode. In addition, the supervision strength has significantly adjusted the relationship between fundamental facilities, logistics after sales and Starbucks customer satisfaction. Therefore, building a "department supervision + industry self-discipline" supervision system, enhancing the interactive effect of Starbucks live commerce, strictly controlling the product quality of Starbucks and improving Starbucks after-sales service system are feasible suggestions to improve consumer satisfaction under Starbucks live delivery mode and emphasizing the moderating effect of supervision strength on live commerce so as to provide reference for relevant stakeholders involved in live shopping to make optimal decisions, so as to protect the interests of all parties, achieve win-win results.